2012
DOI: 10.4103/0976-9668.101907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary immunoglobulin A levels in tobacco smokers and patients with recurrent aphthous ulcers

Abstract: Objectives:The aim of the present study was to analyze the influence of smoking on the salivary immunoglobulin response in smokers and to evaluate the salivary immunoglobulin A in patients with recurrent aphthous ulcers.Materials and Methods:The study included total of 80 subjects, of whom 40 were having history of chronic smoking habit, 20 were clinically diagnosed cases of recurrent aphthous ulcer and 20 were in the control group. Sample of unstimulated saliva was collected, centrifuged and analyzed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…One study reported a significant inverse correlation between salivary IgA concentrations and current level of smoking, but no correlation between smoking and salivary IgG or IgM concentrations . By contrast, another study reported there to be no correlation between salivary IgA levels and frequency or duration of smoking . With regard to serum Igs, no significant correlation was found between IgD levels and duration of smoking .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study reported a significant inverse correlation between salivary IgA concentrations and current level of smoking, but no correlation between smoking and salivary IgG or IgM concentrations . By contrast, another study reported there to be no correlation between salivary IgA levels and frequency or duration of smoking . With regard to serum Igs, no significant correlation was found between IgD levels and duration of smoking .…”
Section: Discussionmentioning
confidence: 98%
“…The aim of the present study was therefore to compare concentrations of IgD, as well as IgG, IgA and IgM, in both serum and saliva samples from smoking and non‐smoking individuals. Furthermore, this was undertaken using a protein microarray assay to quantify the Ig class levels—this relatively recent technique was not used in any of the previous studies referred to above . The protein microarray used was essentially a miniaturized version of a sandwich/capture ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, exposure to incense could potentially have similar effects on the oral environment and on the function and composition of saliva, as observed in tobacco smokers 23,24 . Thus, we could expect that incense use, as with tobacco use, could result in the reduction of saliva by the depletion of oxygen 25 , increased acidity 26,27 , decreased activity and abundances of salivary proteins 28,29 , and lower abundance of Immunoglobulin A (IgA) molecules 30 . We recently reported 19 that cigarette use in this population is strongly related to Proteobacteria and Fusobacteria depletion and enrichment of several taxa within the phyla Synergistetes and Actinobacteria , among others 19 .…”
Section: Discussionmentioning
confidence: 99%
“…IgA is the most represented Ig type in saliva, having a protective action against the oral bacteria (Shilpashree & Sarapur, ; Sistig, Vučićević‐Boras, Lukač, & Kusić, ). However, the results of previous studies on salivary IgA levels of patients with psoriasis or periodontitis are contradictory.…”
Section: Discussionmentioning
confidence: 99%